Optimasi Flow Entries Untuk Mencegah Flow Table Overflow Pada Server Load Balancing Berbasis Software Defined Networking - Agung Wahyu Setio Budi; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software Defined Networking (SDN) is new paradigm in computer network management to replace a complex conventional network into the flexible and efficient network by separating the control plane and data plane.This concept lead the control plane define each of flow to be written into data plane. However, the space in the flow table is limited resource, requires careful management to prevent flow table overflow. This research discusses a flow entries management to prevent flow table overflow in SDN by proposing two mechanism of flow removal, that is flow expiry and flow modification. The flow expiry remove an expired flow based on its time, meanwhile the flow modification will be triggered whenever the flow tablespace is nearly full. The implementation of our proposal carried out on a stateless server load-balancing application on SDN. The evaluation results show that the system is able to prevent flow table overflow. Before implements our proposal, 53% of total packet did not get response from server. After implements our proposal, 100% of total packet can accommodate by flow table and get a service from server. In addition, the reuse of flow entries can reduce the value of network latency.